Teknik Pengambilan Keputusan di SD IT Riyadhoturrohman - Reni Septrisia; Lanni Jurriah; Mhd Reihandra Aziz; Nur Hafikrah; Azizah Rahmadani; Putriana Nasution (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
This research aims to describe decision-making techniques at SD IT Riyadhoturrohman. This paper uses qualitative research. Data collection techniques were carried out using observation, interviews and documentation. The informants for this research include school staff who are directly supported by documentation. Data analysis uses descriptive qualitative starting from data collection, data reduction, data presentation and drawing conclusions. The results of the research are: (1) Multiple Alternative decision making technique, where this decision making technique is a technique for making decisions based on determining the best alternative from several certain criteria; (2) The inhibiting factors in decision making are the lack of teacher cooperation in taking part in decision making, as well as awareness of the teacher's responsibility for giving opinions when making decisions, (3) The solution to the inhibiting factors is to be advised verbally if still It cannot then be reviewed in writing or in the sanctions policy from the school leadership or principal.